Keeping TRACK(s) of inclusive interactions in ECEC services: the affordances of video-analysis for professional development - Lucia Balduzzi; Valentina Migliarini; Arianna Lazzari (Firenze University Press, 2019)
Recent research shows the growing need of using video-analysis in qualitative educational research. Video-analysis offers possibilities for representing Early Childhood Education and Care (ECEC) professionals' practices, and for becoming a mediational and epistemological tool of their on-going knowledge construction about inclusion and equity. This paper presents initial findings from a case study conducted in Bologna, Italy, using video-analysis as a tool for ECEC practitioners' active learning and professional development. Results from the study show how video (recording and analysis) help practitioners (re)thinking their interactions with children and stimulate reflections on their conceptualization of inclusive practices. Drawing on a European trans-national project funded by the Erasmus Plus Program, this paper argues the relevance of video-elicited discussions and focus groups to help providing significant feedback to educators, as well as creating a digital repository of inclusive practices.   Registrare interazioni inclusive nei servizi per l'infanzia: video-analisi e formazione degli insegnanti. Ricerche recenti dimostrano l'importanza dell'uso della video-analisi nella ricerca educativa qualitativa. L'analisi dei video offre la possibilità di rappresentare le pratiche di educatori e professionisti che operano nei servizi per la prima infanzia. La video-analisi può diventare uno strumento epistemologico e di mediazione per l'acquisizione di conoscenze sull'inclusione e l'equità. Il contributo presenta i primi risultati di un caso studio condotto in Italia (Bologna) utilizzando l'analisi video come strumento per l'apprendimento attivo e lo sviluppo professionale degli educatori nei servizi per l'infanzia. I risultati dello studio mostrano come la registrazione e l'analisi dei video aiuta gli educatori a (ri)pensare le loro interazioni con i bambini, stimolando rinnovate riflessioni sulla loro concettualizzazione di pratiche inclusive. Basandosi su un progetto di ricerca Europeo finanziato dal programma Erasmus Plus, questo articolo sostiene la rilevanza dei focus group stimolati da video per fornire feedback agli educatori in formazione in servizio, nonché a creare un archivio digitale di pratiche inclusive.